A Formal Model and Verification Problems for Software Defined Networks - V. A. Zakharov; R. L. Smelyansky; E. V. Chemeritsky (Моделирование и анализ информационных систем, 2013)
Software-defined networking (SDN) is an approach to building computer networks that separate and abstract data planes and control planes of these systems. In a SDN a centralized controller manages a distributed set of switches. A set of open commands for packet forwarding and flow-table updating was defined in the form of a protocol known as OpenFlow. In this paper we describe an abstract formal model of SDN, introduce a tentative language for specification of SDN forwarding policies, and set up formally model-checking problems for SDN.